Improving Ga distribution and efficiency of flexible Cu(In, Ga)(S, Se) solar cell using CuGa:Na target route. (May 2019) - Lin, Yi-Cheng; Liu, Kuan-Ting; Hsieh, Tung-Po; Hsu, Hung-Ru
Abstract: In this work, we proposed a novel CuGa-NaF (CuGa:Na) target route to improve Ga distribution and device efficiency of flexible Cu(In, Ga)( S, Se) (CIGSSe) solar cells. Analysis involved characterizing the basic material properties of two absorber layers fabricated using sputtering targets of CuGa:Na or Mo: Na. We assessed the uniformity of Ga and Na distribution in the absorber layers. We also examined the effects of various sputtering parameters and sought to optimize the Na content. Finally, we compared the conversion efficiency of the solar cells fabricated using the two Na addition routes (targets of CuGa:Na or Mo:Na target) with the following structure: metal foil/Cr/Mo/CIGSSe/CdS/i-ZnO/ITO/Al. Experimental results show that the CuGa:Na target improved the Ga distribution on the surface of the CIGSSe absorber compared to the Mo:Na target. When applied at a CuGa:Na/In thickness ratio of 300 nm/300 nm, the conversion efficiency of the two devices was as follows: CIGSSe solar cell with Mo: Na-derived absorber layer (7.5%) and CIGSSe solar cell with CuGa: Na-derived absorber layer (9.81%).